A collection method of motion video motion track based on fuzzy clustering algorithm. (22nd March 2023) - Yang, Honglan; He, Guan
In order to overcome the problems of low spatial accuracy, poor noise reduction ability and high spatial distortion rate of traditional methods, a motion video motion trajectory collection method based on fuzzy clustering algorithm is proposed. The fuzzy clustering algorithm is used to pre-process the motion video to improve the compression ratio of the motion video. The motion point accumulation method is used to extract the image sequences in the motion video. The motion targets are extracted, and the trajectory points of the motion targets are labeled. A new motion trajectory range is established, and the collection of the motion trajectory within the marked range is realised. The experimental results shows that the minimum noise value of the proposed method is only 0.02 dB and 0.03 dB, the spatial distortion rate of designed method is lower; it has better anti-noise effect, and more accurate motion trajectory acquisition results.